2018
DOI: 10.1530/ec-18-0191
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D deficiency in children and adolescents is associated with type 1 diabetes mellitus

Abstract: BackgroundTo investigate the relationship 25-hydroxy vitamin D (25OHD) level among children and in children with type 1 diabetes mellitus (T1DM).MethodsA case–control study was conducted to compare the serum 25OHD levels between cases and controls. This study recruited 296 T1DM children (106 newly diagnosed T1DM patients and 190 established T1DM patients), and 295 age- and gender-matched healthy subjects as controls.ResultsThe mean serum 25OHD in T1DM children was 48.69 ± 15.26 nmol/L and in the controls was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Although a large number of studies have shown that patients with islet autoimmunity or T1D have significantly lower VD levels than healthy controls, low VD blood concentrations measured before the detection of islet autoantibodies were not associated with the progression to overt T1D (56). Moreover, when VD levels were prospectively measured from the 3rd month of life in a group of initially healthy children, patterns in the variation in VD concentrations were similar between those who later developed T1D and those who remained healthy, and VD values were not correlated with the age at seroconversion to autoantibody positivity ( p = 0.79) or disease onset ( p = 0.13) (57).…”
Section: Environmental Factors Potentially Associated With Type 1 Diamentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of studies have shown that patients with islet autoimmunity or T1D have significantly lower VD levels than healthy controls, low VD blood concentrations measured before the detection of islet autoantibodies were not associated with the progression to overt T1D (56). Moreover, when VD levels were prospectively measured from the 3rd month of life in a group of initially healthy children, patterns in the variation in VD concentrations were similar between those who later developed T1D and those who remained healthy, and VD values were not correlated with the age at seroconversion to autoantibody positivity ( p = 0.79) or disease onset ( p = 0.13) (57).…”
Section: Environmental Factors Potentially Associated With Type 1 Diamentioning
confidence: 99%
“…Interestingly, the increased diversity in the gut microbiota composition emerged in parallel with the activation of autoimmunity and the detection of autoantibodies (56). Dysbiosis can occur due to the delivery procedure and is more common in children born by cesarean section.…”
Section: Environmental Factors Potentially Associated With Type 1 Diamentioning
confidence: 99%
“…Recent studies have demonstrated an association between vitamin D deficiency and other conditions, independent from the direct role of vitamin D in calcium and bone metabolism. Vitamin D deficiency during pregnancy has been associated with increased risk of pre-eclampsia [57] and an increased risk of asthma [34] and type 1 diabetes [58] in the offspring of vitamin D deficient mothers, warranting further research to determine possible underlying mechanisms. Ensuring vitamin D adequacy through maternal oral supplementation of vitamin D 3 at a level of 80 µg (3200 IU) per day is safe and would prevent most forms of rickets as well as reducing incidence of some complications of pregnancy that are harmful to the mother and foetus.…”
Section: Discussionmentioning
confidence: 99%
“…1. Finally, 12 case-control studies [21][22][23][24][25][26][27][28][29][30][31][32], two nested case-control studies [33,34], one case-cohort study [28], and one cross-sectional case-control study [35] were pooled in the meta-analysis.…”
Section: Literature Research and Study Characteristicsmentioning
confidence: 99%